Hukum Berinvestasi pada Asuransi Jiwa Syariah Berbasis Unit Link pada PT. Prudential Life Asurance Binjai - Islah Rizky Parinduri; Yusrizal Yusrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
ABSTRACTInsurance is a means of disseminating the â€žÃ¢qilah system to the government, companies, institutions and professional institutions. There are verses of the Koran instructing Muslims to prepare for a better tomorrow by investing in sharia life insurance. Unit Link is a favorite product for tax regulation. If you buy mutual funds/shares directly according to United States law, you will be directly subject to income tax from the profits of the mutual funds/shares and this benefit does not exist in Indonesia. In Indonesia, purchases of mutual funds/shares are not subject to tax so that the tax difference between unit link purchases and mutual fund purchases has not been felt. From this background, there are several problems which are formulated as follows: how is the law investing in unit link-based sharia life insurance? This research uses a qualitative type of library research. The data collection method uses the documentation method, the approach method uses analytical normative juridical and conceptual (concept approach). Methods of data analysis using descriptive method. Analyzing the problems that the researchers have tried to bring out, it can be concluded that the concept of investing in unit-link-based sharia life insurance is the activity of investing assets in the form of assets as tabarru' with an effort to protect each other and help a number of people or parties who provide return patterns facing certain risks through contract in accordance with sharia principles where the unit link becomes an investment instrument; Sharia life insurance is a new type of contract that has never existed during the development of Islamic fiqh, where there are differences of opinion among scholars who prevent and forbid life insurance; and with its current status, life insurance has an intolerant premium, so a life insurance contract is more of a speculative contract that contains elements of gambling (gambling) and betting.Keywords: Syariah Life Insurance, Unit Link